STRESS EVOLUTION ONTO MAJOR FAULTS IN MYGDONIA BASIN - Gkarlaouni, G.C.; Papadimitriou, E.E.; Kilias, A.Α. (Bulletin of the Geological Society of Greece, 2016)
Stress transfer due to the coseismic slip of strong earthquakes, along with fault population characteristics, constitutes one of the most determinative factors for evaluating the occurrence of future events. The stress Coulomb (ΔCFF) evolutionary model in Mygdonia basin (N.Greece) is based on the coseismic changes of strong earthquakes (M≥6.0) from 1677 until 1978 and the tectonic loading expressed with slip rates along major faults. In the view of stress transfer mechanisms, ΔCFF is also calculated onto fault planes, along with the segmented fault zone from Thessaloniki to Gerakarou and N.Apollonia (TG-NAp FZ). Normal fault segments bound the basin from the south and currently compose the most active neotectonic zone. The association of the spatial distribution of seismicity (2000-2014) with the stress enhanced areas is also investigated. Results demonstrate that the earthquake locations are strongly influenced by the stress transfer from past strong earthquakes and their focal properties. Since the stress build-up occurs fast, results are discussed in terms of hazard assessment by defining potential locations for future events.